Comparative vibrational spectra of pilosine and epiisopilosine crystals - Bento, R. R. F.; Silva, L. E. da; Faria, J. L. B.; Freire, P. T. C.; Oliveira, M. C. F. de; Romero, N. R.; Teixeira, A. M. R.; Pontes, Fenelon Martinho Lima [UNESP] (Sociedade Brasileira de Física, 2010)
This paper describes the study of two alkaloids extracted from Pilocarpus Microphyllus (Rutaceae): pilosine and epiisopilosine. These substances have potential application in the treatment of several diseases. In this work FT-Raman and the FT-IR spectra of pilosine and epiisopilosine were investigated at 300 K. Vibrational wavenumber and wave vector have been predicted using density functional theory (B3LYP) calculations with the 6-31 G(d,p) basis set. A comparison with experiment, allowed us to assign most of the normal modes of the crystals.
Keywords: Raman scattering; infrared spectroscopy; normal modes; pilosine; epiisopilosine